Synergistic antitumor effect of a human papillomavirus DNA vaccine harboring E6E7 fusion gene and vascular endothelial growth factor receptor 2 gene. (23rd September 2016) - Gao, Jie; Fan, Lei; Ma, Wei; Xiao, Huan
ABSTRACT: Human papillomavirus (HPV) has been identified as the primary etiological factor in cervical cancer as well as in subsets of anogenital and oropharyngeal cancers. The two HPV viral oncoproteins, E6 and E7, are uniquely and consistently expressed in all HPV‐infected cells and are therefore promising targets for therapeutic vaccination. In order to achieve a synergistic antitumor and anti‐angiogenesis effect, we designed and constructed a novel DNA vaccine that can express the HPV 16 E6E7 fusion protein and VEGFR2 in the same reading frame. A series of DNA plasmids encoding E6E7, VEGFR2 and their conjugates were constructed and injected into mice. The resultant humoral and cellular immune responses were detected by ELISA and enzyme‐linked immunospot (ELISPOT), respectively. To evaluate the antitumor efficacy of these plasmids, tumor‐bearing mice expressing the E6E7 fusion protein were constructed. After injection into the tumor‐bearing mouse model, the plasmid harboring the E6E7 fusion gene and VEGFR2 showed stronger inhibition of tumor growth than the plasmid expressing E6E7 or VEGFR2 alone, which indicated that the combination of E6E7 and VEGFR2 could exert a synergistic antitumor effect. These observations emphasize the potential of a synergistic antitumor and anti‐angiogenesis strategy using a DNA vaccine, which could be a promising approach for tumor immunotherapy.